Genome-wide analysis provides a deeper understanding of the population structure of the Salmonella enterica serotype Paratyphi B complex in Bangladesh. Issue 9 (22nd September 2021) - Rahman, Sadia Isfat Ara; Taylor-Brown, Alyce; Khanam, Farhana; Khan, Ashraful Islam; Horesh, Gal; Dyson, Zoe A.; Begum, Yasmin Ara; Chowdhury, Emran Kabir; Qadri, Firdausi; Dougan, Gordon; Thomson, Nicholas R.
Abstract : The Salmonella enterica serotype Paratyphi B complex causes a wide range of diseases, from gastroenteritis to paratyphoid fever, depending on the biotypes Java and sensu stricto . The burden of Paratyphi B biotypes in Bangladesh is still unknown, as these are indistinguishable by Salmonella serotyping. Here, we conducted the first whole-genome sequencing (WGS) study on 79 Salmonella isolates serotyped as Paratyphi B that were collected from 10 nationwide enteric disease surveillance sites in Bangladesh. Placing these in a global genetic context revealed that these are biotype Java, and the addition of these genomes expanded the previously described PG4 clade containing Bangladeshi and UK isolates. Importantly, antimicrobial resistance (AMR) genes were scarce amongst Bangladeshi S . Java isolates, somewhat surprisingly given the widespread availability of antibiotics without prescription. This genomic information provides important insights into the significance of S . Paratyphi B biotypes in enteric disease and their implications for public health.